Comparative effects of incretin-based therapy on doxorubicin-induced nephrotoxicity in rats: the role of SIRT1/Nrf2/NF-κB/TNF-α signaling pathways - Botros, Sandy R.; Matouk, Asmaa I.; Amin, Amr; Heeba, Gehan H. (Frontiers in Pharmacology, 2024)
Nephrotoxicity represents a major complication of using doxorubicin (DOX) in the management of several types of cancers. Increased oxidative stress and activation of inflammatory mediators have outstanding roles in the development of DOX-induced kidney damage. This study aimed to investigate whether the two pathways of incretin-based therapy; glucagon-like peptide 1 receptor agonist (presented as semaglutide, SEM) and dipeptidyl peptidase-4 inhibitor (presented as alogliptin, ALO) differentially protect against DOX-induced nephrotoxicity in rats, and to clarify the underlying molecular mechanisms. Adult male rats were divided into 6 groups; control (received the vehicle), DOX (20 mg/kg, single I.P. on day 8), DOX+ALO (20 mg/kg/day, P.O. for 10 days), DOX+SEM (12 µg/kg/day, S.C. for 10 days), ALO alone and SEM alone groups. At the end of study, animals were sacrificed, and kidney functions, oxidative stress and inflammatory markers were assessed. Kidney sections were also subjected to histopathological examination. The co-treatment with either ALO or SEM manifested an improvement in kidney functions, as evidenced by lower serum concentrations of creatinine, urea, and cystatin C compared to the DOX group. Lower level of MDA, higher level of GSH and increased SOD activity were observed in either ALO or SEM treated groups compared to DOX group. DOX administration resulted in decreased renal expressions of sirtuin-1 (SIRT1) and Nrf2 with increased NF-κB and TNF-α expression, and these effects were ameliorated by treatment with either ALO or SEM. In conclusion, co-treatment with either ALO or SEM showed reno-protective effect that was mediated by their antioxidant and anti-inflammatory effects via SIRT1/Nrf2/NF-κB/TNF-α pathway. Equally noteworthy is the fact that both pathways of the incretin-based therapy demonstrate an equally positive effect in alleviating DOX-induced renal damage.